Two-Stage Sector Partition Path Planning Method for Automated Fiber Placement on Complex Surfaces. (March 2021) - Gao, Jiaxin; Qu, Weiwei; Yang, Di; Zhu, Weidong; Ke, Yinglin
Abstract: Automated fiber placement (AFP) is an advanced composite manufacturing technology which is widely used in the production of complex shaped aircraft components. However, on the surface with large curvature, the fiber compaction performance is poor, and the direction deviation and the geodesic curvature of the path increase sharply with the offset distance, resulting in various placement defects. To solve this problem, the influence of the surface curvature on the path performance is studied, and a two-stage sector partition path planning method for AFP on complex surface is proposed in this paper. The constraints of the direction deviation, turning radius and the compaction state of the fiber are comprehensively considered in this method. By analyzing the compaction feature, the distance between the roller and the surface is used to evaluate the compaction condition and an initial partition criterion is established according to the normal curvature of the surface along the roller axis. Then, the quantitative relationship between path performance and offset distance is derived, and the precise sector is determined under the constraints of placement direction and turning radius. The path performance constraints are fully considered in the path generation process, so the iterative process of evaluation–modification is effectively avoided. Simulations and experiments are then carried out on the winglet surface and the results show that compared with the parallel method, the proposed method can significantly improve the direction deviation, turning radius and compaction quality of the placement paths at the cost of gaps/overlaps. Satisfactory placement paths can be obtained with reasonable constraints on the complex surface. Highlights: A new path planning method using two-stage sector partition is established for complex surface. The direction deviation, turning radius and the compaction state are comprehensively considered. Initial partition criterion is the fiber number estimated by the surface curvature along roller axis. The quantitative relationship between path performance and offset distance is established.